DOCA and L-NAME hydrochloride: Their impact on T regulatory cells, macrophage activity, and pro- and anti-inflammatory cytokine profiles in pre-eclampsia animal model - Azmi, Shella ZK.; Christina, Yuyun I.; Dwijayanti, Dinia R.; Rahayu, Sri; Djati, Muhammad S. (Narra Sains Indonesia, 2025)
Deoxycorticosterone acetate (DOCA) and N-nitro-L-arginine methyl ester (L-NAME) hydrochloride have been well-reported as pre-eclampsia inducers due to their ability to mimic hypertension, endothelial dysfunction, and inflammatory response. However, no study has compared the two inducers in developing a mice model of preeclampsia characterized by proinflammatory and anti-inflammatory parameters. The aim of this study was to investigate the efficacy of DOCA and L-NAME hydrochloride in inducing pre-eclampsia in pregnant mice, focusing on the expression of regulatory T cells (Tregs), macrophages, anti-inflammatory cytokines TGF-β, and pro-inflammatory cytokines (IL-6 and IL-1β). Twenty-seven female BALB/c mice were grouped into three groups (n=9): healthy pregnant mice (NP), pregnant mice induced with DOCA (PD), and pregnant mice induced with L-NAME hydrochloride (PL). L-NAME hydrochloride was orally given to the pregnant mice at 4.464 mg/30 g body weight (BW) every day after five days of gestation. DOCA was injected subcutaneously in 0.1 mL of corn oil at 0.74 mg/30 g BW before mating and 0.38 mg/30 g BW once a week until dissection. Drinking water for PD and PL groups was replaced with 0.9% saline. On day 16 of pregnancy, the lymphocytes were isolated from the spleen to determine the profile of Tregs, macrophages, TGF-β, IL-6, and IL-1β using flow cytometry analysis. The results showed that administering L-NAME hydrochloride in pregnant mice exhibited a significant increase in the relative number of IL-1β and macrophages compared to DOCA (p<0.05). L-NAME hydrochloride significantly reduced the production of TGF-β compared to DOCA (p<0.05). Both DOCA and L-NAME hydrochloride could decrease Tregs and IL-6 levels. This study also found that L-NAME hydrochloride was more effective in inducing pre-eclampsia in pregnant BALB/c mice than DOCA indicated by the highest increase in pro-inflammatory cytokines and macrophage activity and a low anti-inflammatory cytokine. The present study provides a foundation for understanding the pathophysiological mechanisms of preeclampsia in the inflammatory pathway; however, further exploration of other mechanisms, markers, and target proteins can deepen insights into its development.